Impact of natural disaster on human capital, biodiversity loss and infectious disease - Pritam Singh, Harpaljit Kaur (2018)
Natural disasters have become among the most pressing issues facing the world today. It is becoming more recurrent and more intense worldwide in the recent decades due to changes in the global climatic environment and has affected not only the human development drastically but has tremendous impact on biodiversity loss and on the increasing risk of infectious diseases. Many studies have been done at micro level, however, to the author’s knowledge; the number of studies carried out to empirically investigate the impact of natural disasters, at a macro level, on human capital is rather limited, exception to Cuaresma (2010) and McDermott (2012). The study employed two methodologies to achieve its objectives. For the first objective, the study employed system Generalized Method of Moment (GMM) to examine the impact of total disasters and four individual types of natural disasters (floods, storm, drought and earthquake) on secondary and tertiary school enrollment rates using panel data for 104 countries over the period 1970 to 2014. For robustness check, each natural disasters was measured using four proxies; the number of occurrences, number of deaths, number of people affected and total damages. The analysis is then extended by including a measure of the one-period lagged natural disaster whereby all the natural disaster variables are estimated with a lag to capture the delayed effect of these variables on the enrollment rates. Employing the system Generalized Method of Moment (GMM) model, we find that the number of occurrences of natural disasters and disaster related losses (number of deaths, number of people affected and total damages) decreases the enrollment rates. The magnitude of these effects differs significantly across the types of natural disasters and disasters like storm and floods have a delayed effect on secondary school enrollment. For the second objective, ordinary least square and quantile regression are employed to study the effect of natural disasters on biodiversity loss. Biodiversity is declining rapidly in many parts of the world and during this same period, the population growth of humanity has nearly doubled, rapid urbanization, logging and conversion for agriculture have caused forest to be at jeopardy and have increased the rates of species extinction globally. In the present study, OLS and quantile regression were employed. The findings indicate that occurrences and damages affected positively all the four threatened species for all the quantiles differently. The third objective of the study employed system GMM to examine the effect of natural disasters on the prevalence of malaria cases in 79 countries during the period 2008 to 2014. For robustness check, natural disaster was measured using two proxies; the number of occurrences and the number of people affected for total disasters and floods. It is found that positive association exist between these two measures of natural disasters with malaria prevalence throughout the nations. Based from the findings, the study suggests that the government and policy makers place greater emphasis on the importance of disaster preparedness and risk reduction for different level of education. In addition, since education is vital to reduce the cycle of poverty and to improve income and health in the long-term, the government should prioritize the restoration and reconstruction of damaged schools and education related infrastructure, with high quality materials that can withstand the impact of disasters, hence reduce the prolonged disruption to schooling. Policy makers should also create new alternative places for the students to study and establish campaigns to create awareness to the public about the importance of continuation of schooling after disaster. Bolder steps need to be taken in order to conserve and preserve the species, flora and fauna through the efforts of reforestation such as the mangrove project, which will dampen the impact of disaster related losses caused by tsunamis and hurricanes and create job opportunities. With the rapid increase in population growth and the value of economic activity, the government need to increase protected areas and restoration projects besides enforcing strict laws, to ensure the safety of the threatened species. These steps will help the economy of the country by attracting tourism. Finally, policy makers and government should improvise prevention and control measures for minimizing infectious diseases, especially in the aftermath of natural disasters.